Recent developments and the new direction in soft-computing foundations and applications : selected papers from the 6th World Conference on Soft Computing, May 22-25, 2016, Berkeley, USA /: selected papers from the 6th World Conference on Soft Computing, May 22-25, 2016, Berkeley, USA. (2018) - Unknown
No abstract available